IMPLEMENTATION OF A MACRO EXCEL-BASED ACCOUNTING INFORMATION SYSTEM FOR HOMESTAYS IN UNDISAN TOURISM VILLAGE BANGLI REGENCY - Parwati, Ni Made Diah; Rukmiyati, Ni Made Sri; Tuwi, I Wayan; Septiviari, Anak Agung Istri M.; Sumariati, I Dewa Ayu Rai (Transpublika Publisher, 2024)
This research explores the development of an accounting information system application tailored for homestays, focusing on using Macro Excel. Through field research methods, this research shows that the development of this application can overcome the problems of manual practice in recording petty cash in the Undisan Bangli Tourism Village. Macro Excel was chosen as a solution to increase the efficiency and accuracy of homestay financial administration. The positive contribution can be seen in the ease and reliability of preparing petty cash financial reports and the efficiency of time and energy for homestay managers. Suggestions for future research include further testing of this application in various usage scenarios, integration of additional features, and expansion of the research to other locations. Hopefully, this research can become a basis for further innovation in modern and technology-based homestay management.